DNA binding protein CgIkaros-like regulates the proliferation of agranulocytes and granulocytes in oyster (Crassostrea gigas). (November 2021) - Sun, Wending; Song, Xiaorui; Dong, Miren; Liu, Zhuyun; Song, Ying; Wang, Lingling; Song, Linsheng
Abstract: DNA-binding protein Ikaros is a major determinant of haematopoietic lineage, especially in the development, differentiation and proliferation of lymphocytes. In the present study, a Ikaros homologue (designed as Cg Ikaros-like) was identified and characterized as a vital determinant in the proliferation of haemocytes during haematopoiesis of Pacific oyster Crassostrea gigas . The complete coding sequence of Cg Ikaros-like was of 1329 bp encoding a predicted polypeptide of 442 amino acids with four ZnF regions, locating at the C-terminus and N-terminus respectively. The highest expression level of Cg Ikaros-like mRNA was found in gills, followed by haemocytes and gonad. The mRNA transcripts of Cg Ikaros-like could be detected in all the haemocytes with higher abundance in semi-granulocytes and agranulocytes. Cg Ikaros-like protein was localized in both of cytoplasm and nucleus with higher abundance in nucleus of oyster haemocytes. The mRNA and protein expression levels of agranulocyte marker Cg CD9, granulocyte marker Cg AATase, cell cycle related gene Cg CDK2, Notch receptor Cg Notch and Notch target gene Cg Hes1 all increased significantly ( p < 0.05) after Cg Ikaros-like was interfered by siRNAs, which were about 27.33-, 2.63-, 24.34-, 4.45- and 6.08-fold of that in the siRNA-NC control group, respectively. While the transcripts of Cg GATA3 and Cg Runx did not change significantly after Cg Ikaros-like was interfered. These results demonstrated that Cg Ikaros-like functioned as a transcription factor combined with Notch pathway to mediate Cg CDK2 and regulate the proliferation of oyster haemocytes. Highlights: An Ikaros homologue was identified from the Pacific oyster C. gigas. as a transcription factor involved in haematopoiesis. Cg Ikaros mRNA was highly expressed in haemocytes, and its protein was distributed in both cytoplasm and nucleus. Cg Ikaros could inhibit the proliferation of haemocytes by regulating Cg CDK2 combined with the Notch pathway.